SCYL1 variants cause a syndrome with low γ-glutamyl-transferase cholestasis, acute liver failure, and neurodegeneration (CALFAN) - Lenz, Dominic; Thiel, Christian; Straub, Beate Katharina; Harting, Inga; Dimitrov, Bianca; Kotzaeridou, Urania; Kölker, Stefan; Hoffmann, Georg F.; Staufner, Christian (Genetics in medicine, 2018)
Purpose: Biallelic mutations in SCYL1 were recently identified as causing a syndromal disorder characterized by peripheral neuropathy, cerebellar atrophy, ataxia, and recurrent episodes of liver failure. The occurrence of SCYL1 deficiency among patients with previously undetermined infantile cholestasis or acute liver failure has not been studied; furthermore, little is known regarding the hepatic phenotype. Methods: We aimed to identify patients with SCYL1 variants within an exome-sequencing study of individuals with infantile cholestasis or acute liver failure of unknown etiology. Deep clinical and biochemical phenotyping plus analysis of liver biopsies and functional studies on fibroblasts were performed. Results: Seven patients from five families with biallelic SCYL1 variants were identified. The main clinical phenotype was recurrent low γ-glutamyl-transferase (GGT) cholestasis or acute liver failure with onset in infancy and a variable neurological phenotype of later onset (CALFAN syndrome). Liver crises were triggered by febrile infections and were transient, but fibrosis developed. Functional studies emphasize that SCYL1 deficiency is linked to impaired intracellular trafficking. Conclusion: SCYL1 deficiency can cause recurrent low-GGT cholestatic liver dysfunction in conjunction with a variable neurological phenotype. Like NBAS deficiency, it is a member of the emerging group of congenital disorders of intracellular trafficking causing hepatopathy.